ASSESSMENT OF TRANSPORT INFRASTRUCTURE AND means of transport VULNERABILITY IN CIVIL AVIATION - N. I. Ovchenkov; L. N. Elisov (Научный вестник МГТУ ГА)
This paper investigates the problem of assessment of the vulnerability of transport infrastructure and means of transport as applied to civil aviation. The specific character of civil aviation is taken into account. An approached to vulnerability assessment, based on the concept of quality is offered. Show the interdependency of the concepts of vulnerability and quality is shown.